2022
DOI: 10.32890/mjli2022.19.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Senior High School Teaching: A Phenomenological Inquiry

Abstract: Purpose - This study aims to explore the teachers’ lived experiences in Senior High School teaching.The K to 12 program is one curricular reform in the Philippines to ascertain that basic education graduates possess the required competencies at par with the international standards. Methodology - In this qualitative study, 15 Senior High School (SHS) teachers’ lived experiences were explored to arrive at the essence of SHS teaching at the onset of curriculum implementation. Using Husserlian phenomenological des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the other hand, according to key informants, they move from individual analysis to a collective analysis, contrasting experiences with their peers and involving their own students. In view of the above, Bacus & Alda (2022), expose the concern for the effects of teaching on students. Likewise, critical and reflective aspects can focus not only on practical analysis, but also on questioning the dominant models (Sathorar & Geduld, 2018) and thus contextualize the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, according to key informants, they move from individual analysis to a collective analysis, contrasting experiences with their peers and involving their own students. In view of the above, Bacus & Alda (2022), expose the concern for the effects of teaching on students. Likewise, critical and reflective aspects can focus not only on practical analysis, but also on questioning the dominant models (Sathorar & Geduld, 2018) and thus contextualize the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Kılıç and Kaymakcı (2019) concluded that instructors chose professional development activities that were specialized and relevant to their teaching methods. Although instructors receive capacity -building training and seminars to give them the necessary content and pedagogical abilities, a study by Bacus and Alda (2022) found that some teachers still feel that need-specific training is insufficient. Teachers also reported that repeated topics were not beneficial to their teaching practices, and they were, therefore, less likely to attend such activities.…”
Section: Teachers' Motivation and Demotivation In Engaging In Pd Acti...mentioning
confidence: 99%
“…In the academic year (AY) 2017-2018, after two years of employing the senior high school (SHS), many studies were conducted but not focused on teachers' experiences and self-assessment. These were some of the study's recommendations: related training geared toward teachers' professional growth, conducting consistent onsite observing, and providing need-based backing and resources for teachers' up-skilling and re-skilling (Bacus and Alda, 2022). After five years of implementation, what are the new curriculum's different positive and negative impacts?…”
Section: Introductionmentioning
confidence: 99%